Experimental and computational evidence on conformational fluctuations as a source of catalytic defects in genetic diseases. Issue 63 (20th June 2016) - Fuchs, Julian E.; Muñoz, Inés G.; Timson, David J.; Pey, Angel L.
Abstract : Catalytic mutants causing inherited type III galactosemia alter active site structural dynamics and shift the native conformational equilibrium towards inactive conformations. Abstract : Theoretical and experimental evidence has shown that protein function, regulation and degradation are intrinsically linked to the dynamic and fluctuating nature of protein ensembles. However, the effect of missense mutations on catalytic performance are often interpreted from conformational analyses derived from X-ray crystallography, molecular dynamics and modeling, while effects on conformational fluctuations at the active site as the source of catalytic defects are rarely investigated. Here, we explore the role of conformational fluctuations in the catalytic efficiency of WT and three missense mutations in the UDP-galactose 4′-epimerase (GALE) protein causing type III galactosemia. Using comprehensive molecular dynamics simulations and small angle X-ray scattering we correlate low NAD + binding affinity in some mutants with an increased population of non-competent conformations for NAD + binding. Proteolysis studies combined with thermodynamic calculations reveal that mutations affecting GALE catalytic performance favor larger conformational fluctuations at the N-terminal domain and NAD + binding site, shifting the equilibrium towards non-binding competent states in the native ensemble. Therefore, we provide a novel ensemble-based thermodynamic mechanism to explain catalytic defects caused by missense mutations that links large and transient conformational fluctuations and loss of catalytic efficiency and substrate/coenzyme affinity. In the context of this mechanism, we propose that allosteric ligands aimed at modulating these transient conformational fluctuations might correct catalytic defects in inherited metabolic diseases, representing a different approach to current small ligand therapies which target the low stability, but not catalytic defects, of mutations.